2020
DOI: 10.1016/j.chiabu.2020.104699
|View full text |Cite
|
Sign up to set email alerts
|

Stress and parenting during the global COVID-19 pandemic

Abstract: Background: Stress and compromised parenting often place children at risk of abuse and neglect. Child maltreatment has generally been viewed as a highly individualistic problem by focusing on stressors and parenting behaviors that impact individual families. However, because of the global coronavirus disease 2019 (COVID-19), families across the world are experiencing a new range of stressors that threaten their health, safety, and economic well-being. Objective: This study examined the effects of the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

81
1,099
9
70

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,108 publications
(1,259 citation statements)
references
References 71 publications
81
1,099
9
70
Order By: Relevance
“…Individuals with strong support from spouses and employers and a positive work-life balance during the pandemic also report less marital and parental stress than those with lower levels of support and less balance (Chung, Chan, et al, 2020). Similarly, Brown et al (2020) found that parents who received more support from others reported less perceived stress. Whereas some commentators suggest that greater time together under pandemic stress may result in greater con ict in some families (Buttell & Ferreira, 2020; Campbell, 2020), others note the potential for greater closeness in other families (Gambin et al, 2020).…”
Section: Protective Factorsmentioning
confidence: 87%
See 3 more Smart Citations
“…Individuals with strong support from spouses and employers and a positive work-life balance during the pandemic also report less marital and parental stress than those with lower levels of support and less balance (Chung, Chan, et al, 2020). Similarly, Brown et al (2020) found that parents who received more support from others reported less perceived stress. Whereas some commentators suggest that greater time together under pandemic stress may result in greater con ict in some families (Buttell & Ferreira, 2020; Campbell, 2020), others note the potential for greater closeness in other families (Gambin et al, 2020).…”
Section: Protective Factorsmentioning
confidence: 87%
“…As one key example of a broad pandemic stressor, families around the world report being affected by quarantine and mandatory social distancing (Brooks et al, 2020). These quarantine practices result in challenges to work-family balance through less support for parents from employers and spouses Craig & Churchill, 2020), unemployment (Brown et al, 2020), online schooling demands (Segre et al, 2020), and increased caregiver burden (Russell et al, 2020;Patrick et al, 2020). Although quarantine may entail spending more time at home with family, Ammar et al (2020) found that family members in Asia, Africa, and Europe reported feeling more socially isolated as a result of fewer opportunities to visit with family outside of the home as well as friends and neighbors during quarantine.…”
Section: Pandemic Life Events As Family Stressorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Female and unmarried parents reported higher rates of worsening mental health (Patrick et al, 2020). In the US, parents who perceived more support from others experienced lower stress (Brown, Doom, Lechuga-Peña, Watamura, & Koppels, 2020). Additionally, the more difficulties Italian parents perceived regarding quarantine (e.g., difficulties in finding a relaxing space alone, time for the partner and for kids, and to do leisure activities), the more their well-being was undermined (Spinelli, Lionetti, Pastore, & Fasolo, 2020).…”
Section: Covid-19 Affects Families' Well-beingmentioning
confidence: 99%